O35 Screening for lynch syndrome in cases of colorectal cancer: identifying barriers in a fast-track pathway. (19th June 2022) - Lee, Tom; Glover, Eleanor; Ngu, Lena; Gibson, Philip; Sheth, Harsh; Gallon, Richard; Martin, Richard; Jackson, Michael; Mills, Sarah; Burn, John
Abstract : Introduction: Lynch Syndrome accounts for 2–3% of all colorectal cancers. 1 in 200 individuals are thought to be affected but fewer than 5% of these know they have the condition. NICE guidance in 2017 recommended that all people diagnosed with colorectal cancer are tested for Lynch Syndrome. This study explores the implementation and efficacy of a testing pathway, with a focus on identifying barriers to achieving high levels of test coverage and onward referral when indicated. Methods: The initial part of the study is a retrospective analysis of all patients diagnosed with colorectal cancer at a large NHS Trust in a 5-year period that encompassed the implementation and refinement of a fast-track microsatellite instability (MSI) testing pathway. The second part of the study involves ascertaining the viability of using fresh endoscopic biopsies for molecular MSI testing with a multiplex 12-marker polymerase chain reaction (mPCR) assay. Results: In the study period there were 1688 new diagnoses of colorectal cancer, of whom 906 (62.7%) underwent an MSI assay. 283 (31.2%) of MSI tests were performed on a fresh endoscopic biopsy. The remainder were performed on a paraffin curl of the endoscopic biopsy containing >30% of pathologically confirmed malignant tissue. The median turn-around time (TAT) from sample submission to result of MSI testing was 13 days (IQR 10, 19). 40 MSI high, BRAF negative cases were identified. 29 (72.5%) of these were referred for assessment by the regional genetic service. DNA analysis was performed in 19 (65.5%) of the referred cases with an MMR mutation identified in 7 cases. A greater proportion of new cases were tested following introduction of reflex MSI testing by the histopathology lab. Analysis of four LS composite biopsy blocks demonstrated a clear MSI signal regardless of tumour content of individual endoscopic biopsies. MSI testing was less likely to occur in frailer patients, advanced stage at presentation and those diagnosed radiologically. Conclusions: This study demonstrates a model for fast-track MSI testing to facilitate screening for Lynch Syndrome and to inform surgical and oncological decision making early in the colorectal cancer pathway. Identifying factors that impact negatively on testing coverage and onward referral enables the pathway to be modified to optimise detection of Lynch Syndrome.